An Evaluation of the Effect of Graphene Oxide-Gold Nanocomposite on HepG2 Cell Line - Sh Kazemian; SR Mohebbi; T Naji; H Asadzadeh Aghdaei; MR Zali (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2022)
Background and Objective: One of the most important effects of nanomaterials on cells is the induction of programmed cell death (apoptosis). The aim of this study is to investigate the toxicity of graphene oxide-gold nanoparticles and to evaluate the expression of caspase 3 gene in HepG2 liver cancer cell line. Methods: In this experimental study, hepatocellular carcinoma cell line (HepG2) was prepared from Pasteur Institute of Iran. Cells were treated with concentrations of 10 to 500 µg/ml Gold-rGO and untreated cells were used as control. The level of caspase 3 gene expression and cell viability were investigated and compared within 24 and 48 hours in three groups of A, B and control (C). The effect of concentration was investigated by XTT method and acridine orange ethidium bromide staining. Caspase 3 gene expression was measured by relative quantification using real time PCR test. Findings: Based on XTT results, EC20, EC50, EC80 values were calculated as 386.420, 90.680, 24.151 µg/ml in 24 hours and 358.146, 89.536, 22.384 µg/ml in 48 hours. Examining the level of caspase 3 gene expression change in these concentrations compared to untreated cells showed mean fold changes (mean±SEM) of 3.436±1.022 in 24 hours and 4.054±0.02 in 48 hours, according to which the level of gene expression changes significantly. The viability of control cells (C) compared to cells treated with concentrations higher than 50 μg/ml (B) has a relative increase, which was statistically significant (p<0.0001). Examination with AO/EB staining to determine the level of apoptosis showed a higher level of apoptosis with increasing dose. Conclusion: The results of the study showed that shorter times and lower concentrations should be used in the application of this nanoparticle.